PRODUCTION OF FOWLPOX VACCINE VIRUS IN CHICK EMBRYO DERMAL TISSUE CULTUE - Sadik Mohammed, Ghanima (The Iraqi Journal of Veterinary Medicine, 1996)
Chick embryo dermis (CED) cell cultures were prepared from skinpeeled off from 12 day old specific pathogen free (SPF) embryo. The cultures were grown in 199 medium containing 5 % calf serum and 10% trypose phosphate broth (TPB). For primary cultures, suspensions containing 8 x 105 cells per ml were seeded in Roux bottles, culture tubes and 2 oz plastic bottles. Cell culture passaged 3-5 times without muh difficulty. Canadian vaccine strain of lowlpox virus was propagated satisfactorily in CED subcultures. Cytopathic effect (CPE) was characterized by rounding of cells, ballooning of a few infected cells and frmation of intracytoplasmic inclusion bodies. The virus titers were in the order of 107.6 TCD 50 per 0.1 ml. Three experimental batches of cell culture adopted virus were prepared to be tested for immunization of susceptible birds. These batches were titrated in CED cultures, embryonated SPF eggs and susceptible chickens. The titers were higher on CED cultures. Four weeks old chickens vaccinated with approximately 105 TCD 50 developed good takes and remained apparantly healthy during the period of observations. Protection was demonstrated against challenge with virulent fowlpox virus. Advantages of production of fowlpox vaccine in CED cultures instead of embryonated eggs were outlined briefly.